Նոր մանրամասներ Անդրկովկասից հայերի 1949ի աքսորի մասին - Գալստեան, Սեդա (տպ. Atlas)
In the process of researching the archive of the 1st secretary of the Communist Party of Armenia, Anton Kochinyan, kept in the Museum of the History of Armenia, our attention was drawn to one important manuscript signed personally by Kochinyan, which was written by the secretary a few months before his death in February 1989. This document covers not only the post-war period, repatriation in 1946-48, but also provides us with details about the mass exile in 1949. According to the evidence, 2754 families were deported to the Altai Territory. The value of this document lies in the fact that its author, being the 3rd secretary of the Communist Party of Armenia at that time, was personally in Leninakan and became acquainted with the situation. It is a regrettable fact that those born in Western Armenia - Kars, Sarikamish and other areas west of the Soviet Armenian border were considered foreigners and were subjected to deportation. The details presented allow us to draw conclusions and comment on the period using these new manifestations of Stalin's repressions and the Cold War.
Keywords: Հրապարակումներ; Աքսոր